Fibre quality of Huacaya and Suri alpacas from the breeding stock of Ocongate, Cusco, Peru - Llactahuamani, Isabel (2020)
The aim of this study was to estimate five technological characteristics of white alpaca fibre in Huacaya and Suri breeds, from the breeding stock of four communities of the Ocongate district, Quispicanchi province, Cusco Region, Peru. Fibre samples were taken from the middle ribs, left flank of 238 animals of the two breeds, of both sexes and of various ages. An Optical Fibre Diameter Analyzer (OFDA 2000) was used to determine the fibre diameter (DF), coefficient of variability of the fibre diameter (CVDF), comfort factor (FC) and curvature index (IC). The evaluation of the fibre tensile strength (RT) was done with the IWG Staple Length & Strength Instrument. The effects of breed, sex, age, and community on DF, CVDF, FC, IC, and RT were estimated with a factorial arrangement, as well as phenotypic correlations between the evaluated variables. Significant differences were found for DF, CVDF, FC, IC and RT (p<0.05) for the breed factor. Sex was significant (p<0.05) for CVDF and age (p<0.05) for DF and FC. The communities showed differences for DF and RT (p<0.05). Significant positive relationships were found between DF with CVDF, FC with IC, and IC with RT; and negative between DF with FC and IC, and CVDF with FC, IC and RT. The alpacas of the communities under study produce a good quality of fibre and have great potential for variability for their genetic improvement.